2021
DOI: 10.3390/microorganisms9010183
|View full text |Cite
|
Sign up to set email alerts
|

Novel Models of Streptococcus canis Colonization and Disease Reveal Modest Contributions of M-Like (SCM) Protein

Abstract: Streptococcus canis is a common colonizing bacterium of the urogenital tract of cats and dogs that can also cause invasive disease in these animal populations and in humans. Although the virulence mechanisms of S. canis are not well-characterized, an M-like protein, SCM, has recently identified been as a potential virulence factor. SCM is a surface-associated protein that binds to host plasminogen and IgGs suggesting its possible importance in host-pathogen interactions. In this study, we developed in vitro an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…24,30 To date it is unclear what role subtypes of scm have in virulence and recent evidence suggests any contribution would be modest. 25 The ability to form biofilms has been investigated in S canis as this allows bacteria to survive stressful events. A recent study characterized S canis ST21 and the presence of the ap1 gene was shown to be linked to biofilm production ability in this species.…”
Section: Discussionmentioning
confidence: 99%
“…24,30 To date it is unclear what role subtypes of scm have in virulence and recent evidence suggests any contribution would be modest. 25 The ability to form biofilms has been investigated in S canis as this allows bacteria to survive stressful events. A recent study characterized S canis ST21 and the presence of the ap1 gene was shown to be linked to biofilm production ability in this species.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that CC13 may be a group of highly virulent strains prone to cause disease in dogs. Although there have been reports of toxic shock syndrome caused by S. canis in dogs [ 28 , 29 ], few toxins from S. canis have been reported [ 30 , 31 ]. Because CC13 is likely to have toxic factors that are pathogenic to dogs, analyses of this cluster will likely identify virulence factors such as the s erythrogenic toxins of S. pyogenes .…”
Section: Discussionmentioning
confidence: 99%
“…Although according to some studies SCM appears to be linked to S. canis virulence (Fulde et al, 2011a(Fulde et al, , 2013, recent findings, based on comparisons between a wildtype strain and an SCM-deficient mutant, questioned the role of SCM in clinical infection (Cornax et al, 2021). The SCM-deficient mutant showed reduced ability to form biofilms compared to the wildtype, but haemolytic activity and survivability in the presence of aminising and oxidising agents were not impacted by the lack of scm.…”
Section: Virulence Mechanismsmentioning
confidence: 98%
“…When tested in vivo, the wildtype strain and the mutant were equally virulent in mouse models of dermal and systemic infection. The SCM-deficient strain, however, showed reduced adhesion and persistence in a murine model of vaginal colonisation when compared to the wildtype, suggesting that SCM might confer fitness advantages in particular anatomical sites (Cornax et al, 2021). Overall, the role of SCM as a virulence factor in S. canis is unclear with recent evidence suggesting a marginal involvement in disease progression.…”
Section: Virulence Mechanismsmentioning
confidence: 99%